2009
DOI: 10.1103/physreva.79.032716
|View full text |Cite
|
Sign up to set email alerts
|

Method for producing ultracold molecular ions

Abstract: We propose a new method for the production of ultracold molecular ions. This method utilizes sympathetic cooling due to the strong collisions between appropriately chosen molecular ions and laser-cooled neutral atoms to realize ultracold, internal ground-state molecular ions. In contrast to other experiments producing cold molecular ions, our proposed method efficiently cools both the internal and external molecular ion degrees of freedom. The availability of an ultracold, absolute ground-state sample of molec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…However, in a recent study5, sympathetic cooling through collisional interaction with laser-cooled atoms was demonstrated to be an alternative and efficient approach to quench molecular ion vibrational motion. Although this result was predicted based on a semi-classical argument6, it had not been verified by detailed quantum mechanical calculations. Further, it was not known how widely this technique could be applied, nor how to estimate its efficiency for other systems.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…However, in a recent study5, sympathetic cooling through collisional interaction with laser-cooled atoms was demonstrated to be an alternative and efficient approach to quench molecular ion vibrational motion. Although this result was predicted based on a semi-classical argument6, it had not been verified by detailed quantum mechanical calculations. Further, it was not known how widely this technique could be applied, nor how to estimate its efficiency for other systems.…”
mentioning
confidence: 82%
“…The use of the long established close-coupling method6 to study the dynamics of atom-diatom rovibrational inelastic collisions seems at first to be a simple task. However, the deep potential well of the system and both the very small vibrational and rotational quanta29 of BaCl + make the size of such calculations tremendous and one could be tempted to consider the use of more approximate alternative approaches like the infinite order sudden approximation32 or the coupled states approximation3334 methods.…”
Section: Methodsmentioning
confidence: 99%
“…We argued in 2009 [13] that the details of the ion-neutral interaction would result in near-unit efficiency for vibrational relaxation, and in 2013 showed that for the case of Ca + BaCl + approximately one in five collisions led to vibrational quenching [41]. A full quantum mechanical treatment of this relaxation has recently been completed and shows good agreement with the measured rate constant [42].…”
Section: Cooling Of Molecular Ion Rotational and Vibrational Motionmentioning
confidence: 92%
“…An interesting alternative to laser cooling for the production of a single-quantum-state molecular sample, is to use a reservoir of ultracold atoms to sympathetically cool the molecules to ultracold temperatures [12][13][14] -in much the same way that cryogenic systems use a helium buffer gas to cool other objects to cryogenic temperatures. In principle, this technique of ultracold-atom sympathetic cooling is completely general since it relies only on the second law of thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Now, a large toolbox for trapping and cooling the motional degrees of freedom of both neutral and charged molecules is available 18 . Although general schemes for cooling the internal degrees of freedom of molecules have been proposed 19,20 , the most general method available at present is cryogenic buffer-gas cooling, which is efficient only for molecules in the vibrational ground state and limits the translational temperature to a few hundred millikelvin 7 . Coherent transfer to the rovibrational ground state [11][12][13][14] is most suitable when most of the molecules are initially in the same quantum state, as is the case for molecules produced by associating cold atoms.…”
mentioning
confidence: 99%